An Integrated, Acceptance-Based Behavioral Approach for Depression With Social Anxiety: Preliminary Results. (July 2014) - Dalrymple, Kristy L.; Morgan, Theresa A.; Lipschitz, Jessica M.; Martinez, Jennifer H.; Tepe, Elizabeth; Zimmerman, Mark
Depression and social anxiety disorder (SAD) are highly comorbid, resulting in greater severity and functional impairment compared with each disorder alone. Although recently transdiagnostic treatments have been developed, no known treatments have addressed this comorbidity pattern specifically. Preliminary support exists for acceptance-based approaches for depression and SAD separately, and they may be more efficacious for comorbid depression and anxiety compared with traditional cognitive-behavioral approaches. The aim of the current study was to develop and pilot test an integrated acceptance-based behavioral treatment for depression and comorbid SAD. Participants included 38 patients seeking pharmacotherapy at an outpatient psychiatry practice, who received 16 individual sessions of the therapy. Results showed significant improvement in symptoms, functioning, and processes from pre- to post-treatment, as well as high satisfaction with the treatment. These results support the preliminary acceptability, feasibility, and effectiveness of this treatment in a typical outpatient psychiatry practice, and suggest that further research on this treatment in larger randomized trials is warranted.